The Effect Of Stress And Work Environment On Generation Z Employee Performance With Job Satisfaction As An Intervening Variable - Riski Supriyanto; Gregorius Nasiansenus Masdjojo (Jurnal Manajemen Bisnis, 2025)
This research aims to analyze the influence of work stress and work environment on employee performance with job satisfaction as a mediating variable. Employee performance is affected by various factors, including work stress, work environment, and job satisfaction. This study uses a quantitative approach, with a sample of 100 respondents selected purposively. Data was collected using Google Forms. The relationships between variables and the mediating role were tested in the data analysis of the Path Analysis model using SmartPLS version 3. The research results show that stress has a negative and significant effect on job satisfaction (β = -0.296); the work environment has a positive and significant effect on job satisfaction (β = 0.477); stress has a negative and significant effect on employee performance (β = -0.368); the work environment has a positive and significant effect on employee performance (β = 0.357); and job satisfaction has a positive and significant effect on employee performance (β = 0.327). Job resources, or a supportive work environment, can enhance performance, but stress in the workplace decreases job satisfaction. This study indicates that management should help employees feel more comfortable in their workplaces and create a supportive work environment to make them happier and more productive. To improve employee productivity and satisfaction, HRD must create stress management programs, create a work environment suitable for the digital generation, and provide flexibility.